Magnificent life of birds - Qamaruz Zaman, Faridah (Universiti Putra Malaysia Press, 2015)
We, humans can learn a lot from studying nature past and present; hence, the importance of a Natural History Museum in each country. The records that are preserved and kept for aeons can give us a glimpse of what was, and prepare us for what will be. Our climate changes and we have to adapt to survive. The lessons from the bird group as pollinators ensure the continuation of the plant species. There are flowers solely pollinated by birds such as that by hummingbirds.